2020
DOI: 10.3311/ppme.16668
|View full text |Cite
|
Sign up to set email alerts
|

Cold Energy Utilization in LNG Regasification System Using Organic Rankine Cycle and Trilateral Flash Cycle

Abstract: "Cold energy" refers to a potential to generate power by utilizing the exergy of cryogenic systems, like Liquefied Natural Gas (LNG), using it as the cold side of a thermodynamic cycle, while the hot side can be even on the ambient temperature. For this purpose, the cryogenic Organic Rankine Cycle (ORC) is one type of promising solution with comprehensive benefits to generate electricity. The performance of this cycle depends on the applied working fluid. This paper focuses on the applicability of some natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…It was proven that each cold source has limitations in the characteristic, operating range, etc. In this modelling, it is also found that propane as a working fluid is still an excellent option to utilize the LNG cold energy at a certain temperature range, similar to the one found in an article [10]. The obtained discussion and modelling results report that, as an alternative fuel, DME appears to be a promising cooling fluid for the geothermal power system with low temperature geothermal sources as well as LNG to expand the operational range of the cycle and increase efficiency.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It was proven that each cold source has limitations in the characteristic, operating range, etc. In this modelling, it is also found that propane as a working fluid is still an excellent option to utilize the LNG cold energy at a certain temperature range, similar to the one found in an article [10]. The obtained discussion and modelling results report that, as an alternative fuel, DME appears to be a promising cooling fluid for the geothermal power system with low temperature geothermal sources as well as LNG to expand the operational range of the cycle and increase efficiency.…”
Section: Discussionsupporting
confidence: 75%
“…The energy input is needed to drive compressors during the liquefaction. In a study [10], it was proved that the consumed energy stored in the LNG can be represented as a cooling potential, which is called cold energy, and then recovered for further usage. After the natural gas is liquefied, it is ready to be efficiently transported by using any kind of transportation i.e., specialized ship, train, trucks, or pipelines because its volume shrinks up to 1/600.…”
Section: Dimethyl Ether Natural Gas Water and Air As Cooling Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some HCs have been tested as working fluids in ORC systems to recover cold energy emitted during liquefied natural gas (LNG) regasification. Using Propane as a working fluid, it is possible to recover up to 332.06 MW of cold energy in the forthcoming LNG regasification system (2020-2023) using seawater as a heat source [35]. According to one research, the application of HCs and their mixture resulted in outstanding cycle performance [36].…”
Section: The Selection Of Working Fluidsmentioning
confidence: 99%
“…217 K can be easily reached in cryogenic cycles (for example using liquid methane, LNG as heat sink), see for example in Ref. [11], while 310 K (almost 33 Celsius) can be obtained by a good air cooling. It is important to remark, that in both cases, the shape of the curves would be the same by choosing higher minimal temperature, only the loops would be smaller and therefore the effect would be less remarkable.…”
Section: Introductionmentioning
confidence: 99%